Genome-wide characterization of L-aspartate oxidase genes in wheat and their potential roles in the responses to wheat disease and abiotic stresses - Feng, Yanqun; Tang, Mingshuang; Xiang, Junhui; Liu, Pingu; Wang, Youning; Chen, Wang; Fang, Zhengwu; Wang, Wenli (Frontiers in Plant Science, 2023)
L-aspartate oxidase (AO) is the first enzyme for NAD+ biosynthesis, which is widely distributed in plants, animals, and microorganisms. Recently, AO family members had been reported in several plants, like Arabidopsis thaliana and Zea mays. The research of AO from these plants revealed that AO played important roles in plant growth, development, and biotic stresses. While the characterization and function of AO proteins in wheat are still unclear. In this study, nine AO genes were identified in wheat genome by sequence alignment and conserved protein domain analysis. These nine wheat AO genes (TaAOs) were distributed on chromosomes 2, 5, and 6 of sub-genome A, B, D. The phylogenetic relationship, conserved motifs, and gene structure analysis showed that nine TaAOs were clustered into three groups, and the TaAOs in each group had similar conserved motifs and gene structure. Meanwhile, the subcellular localization analysis indicated that TaAO3-6D located in chloroplast. The cis-elements prediction showed that a lot of cis-elements in response to ABA, SA, antioxidant/electrophile and photoregulatory were found in TaAO promoters, which suggested that the expression of TaAOs may be regulated by these factors. Finally, the transcriptome and real-time PCR analysis showed that the expression of TaAOs belonging to Group III were greatly induced, while the expression of TaAOs belonging to Group I were greatly suppressed in wheat anthesis infected by F. graminearum. And the inducible expression of TaAOs belonging to Group III in wheat anthesis infected by F. graminearum spikelets were repressed by ABA. In addition, the expression of almost all of TaAOs were induced in cold treatment. These results indicated that TaAOs may participate in wheat to F. graminearum infection and cold stress, and ABA may play a negative role in this process. This study laid a foundation for further investigation of TaAO genes and provided novel insights into their biological functions.